Introduction of indigenous Trichoderma spp. as an induced systemic resistance for Dieback disease control on the Nutmeg seedlings - Susanna, Susanna; Hasnah Hasnah; Karina Shofiya Putri (Talenta Publisher, 2021)
Dieback disease caused by L. theobromae has destroyed nutmeg plantations in Aceh Selatan. Until now, effective control has not been found, while farmer continue to use pesticides that have a negative impact on the environment. Therefore, biological control is an alternative to environmentally friendly control that is being promoted. The purpose of this researth was to control dieback by inducing resistance using three spesies of Trichoderma (local isolates) from the Nutmeg. The three isolates were isolates of plant origin and the nutmeg seeds used are one year old. This researth used a randomized blok design with three species of Trichoderma (T. virens, T. asperellum, and T. harzianum), three doses (5, 10, 15 g), and three replicates.The variables observed were the incubation period, disease incidence, length of stem discoloration, height of the plant, and plant wet weight. Thr result showed that all species of Trichoderma tested were able to induce systemic resistance and promoted plant growth, by inhibiting the incubation period, disease incidence, length of discoloration, increasing height and weight of plant. The treatment of T. virens 10 g was the best treatment result compared to the others.